Spirituality of Communication as Foundation for a Missional Approach to Digital Culture - Daniella Zsupan-Jerome (Religion and Social Communication)
The article seeks to make the case for a Christian spirituality of communication, one that especially addresses the communicative and interpersonal dynamics in digital culture and strives to elevate these toward a disposition of authentic relationality. From this foundation in a Christian spirituality of communication, the article proposes several key theological characteristics as fundamental for a missional approach to digital culture, including revelation, incarnation, communion, truth in context, and announcing hope. The article concludes by proposing a framework for a lived, missional spirituality expressing each of these in the digital context. Living out of this framework offers digital culture greater potential toward human flourishing as a whole.